TREATMENT FOR DEPRESSION AND ANXIETY AMONG ACADEMICS AND HEALTHCARE PROFESSORS AT A MIDWESTERN SANTA CATARINA UNIVERSITY - Pinheiro, Débora Fernandes; Adami, Eliana Rezende; Ogoshi, Rosana Claudio Silva; Rodrigues, Marcielle Aline (Vivências, 2025)
Anxiety and depression disorders can be classified as a group of diseases that cause serious damage to people’s lives, affecting their personal and social lives. Psychotropic medications are the main means of treatment for patients diagnosed with anxiety and depression. The university environment is of great importance in the development of people. However, as it requires a higher level of dedication and study, it can be said that it is a stressful and impactful process in relation to the physical and mental health of students and teachers. The research aimed to evaluate the mental health of academics and professors in the health area, as well as the use of anxiolytics and antidepressants. It is an applied research, qualitative and quantitative nature with exploratory objective, through the application of a questionnaire for data collection. Of the research participants, 90.4% (288) are academics and 9.4% (30) are professors in the health area of the educational institution studied. Where 50.6% (161) use some medication for anxiety and/or depression. The vast majority reported that the indication was for anxiety with 55% (147), followed by depression with 30% (81), insomnia 7% (17), PMS 3% (8) and other indications with 5% (13). It is concluded that the mental health of the research participants is affected, given the above, it is necessary to develop an action plan in order to find solutions and promote mental health care, preventing the increase in the prevalence of mental disorders in universities.